2020
DOI: 10.1155/2020/9063808
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Subjective Health, Happiness, and Life Satisfaction among Young Adults (18-24 Years) in Guyana

Abstract: Abstract. Persistent urban-rural disparity in subjective health and quality of life is a growing concern for healthcare systems across the world. In general, urban population performs better on most health indicators compared with their rural counterparts. However, research evidence on the urban-rural disparity on perceived health, happiness, and quality of life among the young adult population is scarce in South American countries like Guyana. Therefore, in the present study we aimed to investigate whether su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
3
18
0
1
Order By: Relevance
“…Our study goes a step further by examining closely these factors from a gendered perspective; an examination that is virtually non-existent in Ghana. Due to the variations in social norms and biological characteristics, a gendered perspective has been recommended to provide more nuanced information into the associated factors of both men and women's life satisfaction [37][38][39]. The outcome of such attempt has been highlighted by Joshanloo [37] who concluded that sociopolitical, employment-related, and education-related variables were more important to men's life satisfaction whereas women's life satisfaction was associated with variables related to marital status and interpersonal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Our study goes a step further by examining closely these factors from a gendered perspective; an examination that is virtually non-existent in Ghana. Due to the variations in social norms and biological characteristics, a gendered perspective has been recommended to provide more nuanced information into the associated factors of both men and women's life satisfaction [37][38][39]. The outcome of such attempt has been highlighted by Joshanloo [37] who concluded that sociopolitical, employment-related, and education-related variables were more important to men's life satisfaction whereas women's life satisfaction was associated with variables related to marital status and interpersonal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, urban areas occupy more and higher quality material and social resources, therefore people living in urban areas usually enjoy better living standards and medical resources than their rural counterparts. It further explains why self‐rated health scores of urban residents tend to be higher than those of rural areas in terms of material social support (Chen et al., 2017; Wang et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…However, previous studies point out that "subjective health" is a narrower concept than "happiness" and "life satisfaction". 31,32 Also, the scale of EQ-5D-5L used in the present study is strictly regarded as healthrelated QOL, which was developed to measure health outcomes to carry out economic analysis. 17 Considering the single-item life satisfaction and the single-item subjective health measure different aspects, we could suggest these two questionnaires are appropriate if there are two choices for a policy evaluation index.…”
Section: Discussionmentioning
confidence: 99%